2015
DOI: 10.1016/s1995-7645(14)60344-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic, antioxidant and anti—atherosclerogenic effects of aqueous extract of Zanthoxylum heitzii stem bark in diet—induced hypercholesterolemic rats

Abstract: These observations strongly suggest that stem bark aqueous extract of Zanthoxylum heitzii has anti-atherosclerogenic properties, at least partly mediated by antioxidant and hypolipidemic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…These results showed a reduction in atherosclerosis and lipid profiling. This trial concluded that this plant can be used as a medicinal agent to treat atherosclerosis (Ntchapda et al, 2015).…”
Section: Zanthoxylum Heitziimentioning
confidence: 95%
“…These results showed a reduction in atherosclerosis and lipid profiling. This trial concluded that this plant can be used as a medicinal agent to treat atherosclerosis (Ntchapda et al, 2015).…”
Section: Zanthoxylum Heitziimentioning
confidence: 95%
“…Histological studies of cross-sections of the aorta were made at 20× magnification using camera lucida drawings. 29 The histological slides were graded using a semi-quantitative scoring system and were assigned severity grades according to the percentage of foam cells observed in each group; that is, 0 ≤ 1%, 1 < 25%, 2 = 25–50%, 3 = 50–75% and 4 > 75%.…”
Section: Methodsmentioning
confidence: 99%
“…Berdasarkan data Tabel 4 kelompok kontrol negatif terjadi penurunan sebesar 29,94% hal tersebut menunjukkan pakan standar tidak menyebabkan kenaikan kadar kolesterol total, persentase penurunan kadar kolesterol total terbesar 31,29% terjadi pada kelompok rebusan daun mangga dosis 200mg/kgBB. Hal tersebut diyakini karena adanya flavonoid, saponin dan tanin (13). Flavonoid mampu menginhibisi enzim HMG-CoA reductase, sehingga mampu menurunkan kolesterol darah.…”
Section: Penurunan Kadar Kolesterol Totalunclassified